Clinical experience with an active intravascular rewarming technique for near-severe hypothermia associated with traumatic injury - Kiridume, Kazutaka (J Intensive Care, 2014)
Hypothermia and acidosis are secondary causes of trauma-related coagulopathy. Here we report the case of a 72-year-old patient with severe trauma who suffered near-severe hypothermia despite the initiation of standard warming measures and was successfully managed with active intravascular rewarming. The patient was involved in a road traffic accident and was transported to a hospital. He was diagnosed with massive right-sided hemothorax, blunt aortic injury, burst fractures of the eighth and ninth thoracic vertebrae, and open fracture of the right tibia. He was referred to our hospital, where emergency surgery was performed to control bleeding from the right hemothorax. During surgery, the patient demonstrated progressive heat loss despite standard rewarming measures, and his temperature decreased to 32.4°C. Severe acidosis was also observed. A Cool Line® catheter was inserted into the right femoral vein and lodged in the inferior vena cava, and an intravascular balloon catheter system was utilized for aggressive rewarming. The automated target core temperature was set at 37°C, and the maximum flow rate was used. His core temperature reached 36.0°C after 125 min of intravascular rewarming. The severe acidosis was also resolved. The main active bleeding site was not identified, and coagulation hemostasis as well as rewarming enabled us to control bleeding from the vertebral bodies, lung parenchyma, and pleura. The total volume of intraoperative bleeding was 5,150 mL, and 20 units of red cell concentrate and 16 units of fresh frozen plasma were transfused. After surgery, he was transferred to the intensive care unit under endotracheal intubation and mechanical ventilation. His hemodynamic condition stabilized after surgery. The rewarming catheter was removed on day 2 of admission, and no bleeding, infection, or thrombosis associated with catheter placement was observed. Extubation was performed on day 40, and his subsequent clinical course was uneventful. He recovered well following rehabilitation and was discharged on day 46. These findings suggest that active intravascular rewarming should be considered as an aggressive, additional rewarming technique in patients with near-severe hypothermia associated with traumatic injury.